Parasitoid Guilds of Agrilus Woodborers (Coleoptera: Buprestidae): Their Diversity and Potential for Use in Biological Control - Philip B. Taylor; Jian J. Duan; Roger W. Fuester; Mark Hoddle; Roy Van Driesche (Psyche: A Journal of Entomology)
Literature studies in North America (US and Canada), Europe, and Asia (particularly Russia, China, Japan, and the Korean peninsula) were reviewed to identify parasitoid guilds associated with Agrilus woodborers. There are at least 12 species of hymenopteran parasitoids attacking eggs of Agrilus beetles and 56 species (36 genera), attacking Agrilus larvae infesting various host plants in North America, Asia, and Europe. While most of the egg parasitoids (9 species) belong to the family Encyrtidae, a majority of the larval parasitoids are members of five families: Braconidae (24 species/11 genera), Eulophidae (8 species/4 genera), Ichneumonidae (10 species/9 genera), and Eupelmidae (6 species/5 genera). The highest rate of Agrilus egg parasitism (>50%) was exerted by encyrtid wasps (4 species) in North America, Asia, and Europe. In contrast, the highest rate of Agrilus larval parasitism (>50%) was caused by species in two genera of braconids: Atanycolus (North America) and Spathius (Asia), and one eulophid genus, Tetrastichus (Asia and Europe). Reported rate of Agrilus larval parasitism ichneumonids was frequent in North America, but generally low (<1%). Potential for success in biological control of emerald ash borer (Agrilus planipennis Fairmaire) in the USA with North American native parasitoids and old-association Asian parasitoids is discussed.